Chemical and physical properties of Thai traditional shrimp paste (Ka-pi) - Rungsima Daroonpunt, Masataka Uchino, Yoshimasa Tsujii, Machiko Kazami, Daiki Oka, Somboon Tanasupawat (Journal of Applied Pharmaceutical Science, 2016)
Thai traditional fermented shrimp paste (Ka-pi) is widely consumed as condiment and seasoning ingredient in Thailand. Chemical and physical properties of thirteen shrimp paste samples were examined. The water content and water activity (Aw) of the products ranged from 33.95-52.19 % and 0.64-0.72, respectively while salt concentration was 7.00 to 10.85 %. The nitrogen content varied from 2.87 to 6.85 % (w/w). KS1 showed the highest protein content (42.8 %) followed by SP1 and SP3 (42.4 and 41.3 %), respectively. The predominant amino acids were glutamic acid (70.1-593.9 µg/g), lysine (112.7-546.3 µg/g) and leucine (29.5-544.9 µg/g). Total bacterial cell count in the samples ranged from 1.3x103 - 2.9x105 cfu g-1 while lactic acid bacteria (LAB) were not detected. This study will be provided the information for improving the quality of products in manufacture to meet the demand of consumer.
Keywords: Shrimp paste, proximate analyses, amino acids, histamine, water activity.